The issues of national spirituality in Oralkhan Bokey’s journalistic works - Tahan С.Ш.; Sirenova Б.А. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The article looks into the ways the journalistic works by Oralkhan Bokey, while dedicated to contemporaneous topics, reflect on the forms of spirituality and existential experiences of the Kazakh people. The study sheds light on the significance of the sacred names of Abai and Makhambet in the structuring of national spirituality, and highlights how important the deep cultural symbolism of the customs coming from the distant historical past that are rooted in the present life of the people are for explaining their genetic code. Of particular interest is the highest esteem which Bokey the publicist expresses for the oratorical word of the Kazakh society in the past, which, in his understanding, is a national tradition of the spirit that should be carried into the future. The essayistic genre is proclaimed by Bokey as a translator of the people’s spiritual values, and a mirror of the internal world of a contemporary that reflects the latter’s new existential psychology. The essay as an effective form of art of the word and the central genre of journalism should continue the traditions of “kosemsoz”, the national journalism of the past, as a form of national spirituality. Bokey views journalism as belonging with literary fiction as a form of social consciousness, while literature improves its tools for reflecting and studying the collisions of the surrounding world in close contact with journalism.